2018
DOI: 10.3389/fneur.2018.00563
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience Is Associated With Participation Outcomes Following Mild to Severe Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) causes physical and cognitive-behavioral impairments that reduce participation in employment, leisure, and social relationships. Demographic and injury-related factors account for a small proportion of variance in participation post-injury. Personal factors such as resilience may also impact outcomes. This study aimed to examine the association of resilience alongside demographic, injury-related, cognitive, emotional, and family factors with participation following TBI. It was hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 108 publications
3
26
1
Order By: Relevance
“…These results are also in line with multiple studies addressing the need for a biopsychosocial approach to understanding chronic disability after TBI. [8][9][10][11][12][13][14] Nevertheless, several findings were not consistent with our expectations. Although the regression analyses of disability revealed that the final model significantly explained disability, explaining 49.7% (Nagelkerke R 2 ) of the variance and correctly classifying 78.9% of cases, none of the five independent variables in the model were significant.…”
Section: Fear-avoidance and Disability After Tbi 2643contrasting
confidence: 68%
See 1 more Smart Citation
“…These results are also in line with multiple studies addressing the need for a biopsychosocial approach to understanding chronic disability after TBI. [8][9][10][11][12][13][14] Nevertheless, several findings were not consistent with our expectations. Although the regression analyses of disability revealed that the final model significantly explained disability, explaining 49.7% (Nagelkerke R 2 ) of the variance and correctly classifying 78.9% of cases, none of the five independent variables in the model were significant.…”
Section: Fear-avoidance and Disability After Tbi 2643contrasting
confidence: 68%
“…[4][5][6][7][8][9][10][11] Numerous studies have highlighted the potential contribution of psychosocial variables (e.g., personality, coping style, anxiety, and depression) to explain chronic disability. [8][9][10][11][12][13][14][15][16][17][18] The contribution of all these variables suggests the need for a biopsychosocial approach to understandng chronic disability after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous early work showed that stroke outcomes depend on internal buffers, such as overall outlook on life, attitudes regarding the stroke, and ability to cope (39). If it is shown that increased resilience predicts better long-term stroke outcomes, the development of interventions to increase resilience, which is a modifiable construct, may therefore improve cognitive, and emotional outcomes post stroke (18,19,40). Interestingly, neither stress nor resilience was associated with physical outcomes on the Stroke Impact Scale.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, many studies of participation after TBI exclude persons with the most severe impairments and lower levels of function for logistical reasons (e.g., inability to complete self-report questionnaires or primary residence in a non-community setting) (7,8). Alternatively, patients with severe TBI and prolonged impairments may be grouped with less severe patient populations (e.g., moderate TBI) (9), thus potentially masking cohort-specific effects (10,11). Prior studies of severe TBI have focused on emergence from a DoC, global function, or recovery of basic cognitive abilities as primary outcome metrics; however, participation in community-based activities is also considered a measure of successful recovery after TBI.…”
Section: Introductionmentioning
confidence: 99%